2017
DOI: 10.1159/000477330
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA KCNQ1OT1 Promotes Cataractogenesis via miR-214 and Activation of the Caspase-1 Pathway

Abstract: Background/Aims: KCNQ1OT1 regulates the expression of tissue-specific imprinted genes within the Kcnq1 domain. Imprinted genes are positive regulators of apoptosis, one of the forms of cell death related to cataract formation, and thus may provide novel therapeutic targets for cataract treatment. Here, we studied the role of non-coding RNAs(ncRNA) in cataract formation. Methods: Human lens epithelium cells (HLECs) were treated with H 2 O 2, and the expression of KCNQ1OT1 and miR-214 was detected by qRT-PCR. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
(30 reference statements)
5
47
0
Order By: Relevance
“…Guo et al [27] suggested that Kcnq1ot1 could regulate MET expression to promote melanoma growth via binding to miR-153. In our study, the bioinformatics assay predicted that miR-214-3p was a ceRNA of Kcnq1ot1 and had binding sites for both Kcnq1ot1 and caspase-1, which was consistent with the results of previous study on cataracts [18]. We elaborated for the first time the downregulation of miR-214-3p in high glucose-treated cardiomyocytes and the effect of Kcnq1ot1 on DCM via miR-214-3p and caspase-1.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Guo et al [27] suggested that Kcnq1ot1 could regulate MET expression to promote melanoma growth via binding to miR-153. In our study, the bioinformatics assay predicted that miR-214-3p was a ceRNA of Kcnq1ot1 and had binding sites for both Kcnq1ot1 and caspase-1, which was consistent with the results of previous study on cataracts [18]. We elaborated for the first time the downregulation of miR-214-3p in high glucose-treated cardiomyocytes and the effect of Kcnq1ot1 on DCM via miR-214-3p and caspase-1.…”
Section: Discussionsupporting
confidence: 90%
“…2G). The ceRNA networks between Kcnq1ot1 and miR-214-3p and between caspase-1 and miR-214-3p were demonstrated in a previous study using the luciferase assay [18].…”
Section: Silencing Kcnq1ot1 By Sirna Inhibits Pyroptosis Of Cardiomyomentioning
confidence: 67%
See 1 more Smart Citation
“…Critical enzymes involved in DNA methylation, such as DNMT1 and MeCP2, have been identified in human lens epithelial cells (HLECs) [10,11]. Epigenetic regulatory processes, including DNA methylation of CRYAA [9,10,[12][13][14], histone acetylation of SOD1 [15] and long non-coding RNA (lncRNA)-MIAT and KCNQ1OT1 [16,17], have been implicated in the pathological cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, accumulating evidence has been confirmed a close relation between miRNA and the pathogenesis of various ocular diseases, such as pterygium, retinoblastoma, and glaucoma [9,10], as well as cataract. For example, Jin et al [11] revealed that long-chain non-coding RNA KCNQ1OT1 could activate the Caspase-1 pathway through the regulation of miRNA-214, thereby inducing cataract formation. However, miRNA-26a and miRNA-26b could negatively regulate the Jagged-1/Notch signaling pathway to inhibit the formation of cataract, as demonstrated in the study by Chen et al [12].…”
Section: Introductionmentioning
confidence: 99%